Staging systems in bipolar disorder: an International Society for Bipolar Disorders Task Force Report. (25th June 2014) - Kapczinski, F.; Magalhães, P. V. S.; Balanzá‐Martinez, V.; Dias, V. V.; Frangou, S.; Gama, C. S.; Gonzalez‐Pinto, A.; Grande, I.; Ha, K.; Kauer‐Sant'Anna, M.; Kunz, M.; Kupka, R.; et al.
<x xml:space="preserve">Abstract</x> Objective We discuss the rationale behind staging systems described specifically for bipolar disorders. Current applications, future directions and research gaps in clinical staging models for bipolar disorders are outlined. Method We reviewed the literature pertaining to bipolar disorders, focusing on the first episode onwards. We systematically searched data on staging models for bipolar disorders and allied studies that could inform the concept of staging. Results We report on several dimensions that are relevant to staging concepts in bipolar disorder. We consider whether staging offers a refinement to current diagnoses by reviewing clinical studies of treatment and functioning and the potential utility of neurocognitive, neuroimaging and peripheral biomarkers. Conclusion Most studies to date indicate that globally defined late‐stage patients have a worse overall prognosis and poorer response to standard treatment, consistent with patterns for end‐stage medical disorders. We believe it is possible at this juncture to speak broadly of 'early'‐ and 'late'‐stage bipolar disorder. Next steps require further collaborative efforts to consider the details of preillness onset and intermediary stages, and how many additional stages are optimal.